2010
DOI: 10.1097/nmd.0b013e3181e9dd23
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Ability and Mental Health Outcomes Among Deaf People With Schizophrenia

Abstract: Cognition has become prominent in the study of schizophrenia because of its importance for understanding the etiology of the illness and its consequences for living independently. For people with schizophrenia who are also deaf, investigations of cognition and schizophrenia are infrequent. This study examines the role of linguistic ability in relation to cognition, social cognition, and functional outcome among deaf adults with schizophrenia or schizoaffective disorder. The primary finding is that linguistic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…This aligns with research suggesting a relationship between psychiatric disorders and speech/language issues in hearing children [65], including a study of adolescent hearing inpatients where most had some type of language impairment [66]. Additionally, a study of deaf individuals with schizophrenia found better linguistic ability (via earlier ages of sign language exposure) to be associated with greater functional outcomes [67]. While there appears to be general agreement on a higher prevalence of psychopathology in deaf patients, this has commonly focused only upon behavior and adjustment issues [36].…”
Section: Resultssupporting
confidence: 80%
“…This aligns with research suggesting a relationship between psychiatric disorders and speech/language issues in hearing children [65], including a study of adolescent hearing inpatients where most had some type of language impairment [66]. Additionally, a study of deaf individuals with schizophrenia found better linguistic ability (via earlier ages of sign language exposure) to be associated with greater functional outcomes [67]. While there appears to be general agreement on a higher prevalence of psychopathology in deaf patients, this has commonly focused only upon behavior and adjustment issues [36].…”
Section: Resultssupporting
confidence: 80%
“…The chronic schizophrenic subgroup in the present study showed lower amplitude and longer latencies compared to their matched controls and also in comparison to early schizophrenic subgroup when using both types of stimuli. Parallel to these results, Horton [87] recognized that patients with chronic schizophrenia exhibited reduced amplitudes and longer latencies than controls to all frequency changes (5%, 10% and 20%). Moreover, other studies [23,59,83] reported significant reduction of MMN amplitude in chronic schizophrenics when compared to healthy control group and first episodic schizophrenics when using tone stimuli to fMMN and duration deviants MMN (dMMN).…”
Section: Discussionmentioning
confidence: 78%
“…A deaf native signer engaged participants for approximately 1.5 hours in a videotaped structured interview. In a previous study, ASL ability was analyzed in relation to functional outcome in the same deaf subjects evaluated herein (Horton, 2010). The domain proved to be a strong predictor of functional outcome levels, above and beyond the contribution of cognition and social cognition.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, among clinical samples, linguistic and nonlinguistic cognitive abilities are differentially associated with functional outcomes for deaf compared to hearing subjects. For example, nonlinguistic-based cognition (e.g., visuospatial processing) appears to be a more potent predictor of outcome for deaf subjects while linguistic-based cognition (e.g., word memory) may be a more potent predictor for hearing subjects (Horton & Silverstein, 2007; Horton, 2010). Associations between nonlinguistic- and linguistic-based cognition and outcome coincide with the respective population’s reliance on visuospatial versus an aural-oral medium in general.…”
mentioning
confidence: 99%